The relationship between post-traumatic stress disorder, occupational stress, occupational burnout, and mental health in football referees: a national cross-sectional survey in China - Zhao, Liangyu; Zhang, Liguo (Frontiers in Public Health, 2025)
BackgroundThe SARS-CoV-2 pandemic, as a global public health emergency, is widely recognized as a major traumatic event with far-reaching implications for individual mental health. Football referees, as a distinct occupational group, may have been particularly vulnerable to elevated trauma exposure and psychological burden during the pandemic. However, research on the post-pandemic mental health status of this population—and the mechanisms underlying it—remains scarce. This study aims to investigate the relationships and underlying mechanisms among post-traumatic stress disorder (PTSD), occupational stress, occupational burnout, and mental health among Chinese football referees in the aftermath of the SARS-CoV-2 outbreak.MethodsThis cross-sectional study surveyed 344 football referees across 29 provinces in China using standardized questionnaires, including the Impact of Event Scale-Revised (IES-R), Depression Anxiety Stress Scale (DASS-21), Effort–Reward Imbalance Questionnaire (ERI), and the Maslach Burnout Inventory–General Survey (MBI-GS). Data were analyzed using network analysis, exploratory structural equation modeling (ESEM), and bootstrapped mediation testing.ResultsThe prevalence of moderate-to-severe PTSD among football referees was 26.2%, with PTSD significantly negatively predicting mental health outcomes. Network analysis identified effort and emotional exhaustion as central and bridging dimensions across variables. The set-ESEM supported the network analysis findings and demonstrated good model fit. Mediation analyses revealed that occupational stress and occupational burnout served as both independent and sequential mediators in the relationship between PTSD and mental health. Specifically, effort, overcommitment, emotional exhaustion, and cynicism played pivotal roles in this mechanism, while reward and professional efficacy did not exhibit significant mediating effects.ConclusionThis study confirms the applicability of the job demands–resources model and stressor theories, highlighting occupational stress and occupational burnout as critical mediating mechanisms between PTSD and mental health in football referees. These findings provide theoretical and empirical foundations for public health interventions aimed at improving the psychological well-being of referees.